Mengapa Program Pelayanan Kesehatan Peduli Remaja (PKPR) di Puskesmas Kota Magelang tidak Optimal? - Ratna Nur Pujiastuti; Ayun Sriatmi; Nurhasmadiar Nandini (Jurnal Manajemen Kesehatan Indonesia, 2021)
Adolescents are particularly vulnerable to a variety of health risks, especially about sexual promblems and reproductive health problems. The government develops adolenscent health programs in Indonesia by using the Adolenscent Friendly Health Service (PKPR) at the health care level. Adolescent health programs in 2019 at Magelang city has not achieved performance targets, so that it becomes attention to optimizing the PKPR program. This research is to find out cause the implementation of the PKPR program in Magelang Tengah health center which is not optimal with influencing factors. The method of research was qualitative with descriptive approach. The technique of collecting data was through in-depth interviews with subject sellection with purposive sampling criteria. Data analysis used content analysis. Analyzed variables were communication, resources, dispositions or attitudes, and bureaucratic structure. The results showed that implementation of PKPR in health center has not been optimal because have some constraints which influenced by several factors, such as the lack of communication between PKPR teams in coordinating scheduling activities, the understanding and clarity about PKPR program owned by officers was limited, the function of public service room in health center has not been optimal to provided service to adolescent, and monitoring and evaluation was limited. Therefore, it needs to communication and coordination was scheduled regularly so that has a good team management, and needs to monitoring and assessment of SNPKPR by Department of Health regularly in order to know the achievement and factors which influence the unoptimability of implementation PKPR program in the health center.